2019
DOI: 10.1590/0034-7167-2018-0843
|View full text |Cite
|
Sign up to set email alerts
|

Transition to motherhood and mothering for women in wheelchairs: a nursing perspective

Abstract: Objective: To discuss the process of transition to motherhood and mothering of women who are wheelchair users, from the perspective of Afaf Ibrahim Meleis. Method: Qualitative, descriptive, exploratory study conducted with six women in the state of Rio de Janeiro. The Life Narrative method was used, with thematic analysis in the light of Transitions Theory. Results: Developmental and situational transitions occurred and were influenced by personal, community and social factor. Moved mainly by ignorance and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 12 publications
(38 reference statements)
1
11
0
2
Order By: Relevance
“…It was important for them to reflect on child-rearing in the community and build new relationships and connections to get the sense that child-rearing was not only an individual effort, but was also positioned in the community and society through child-rearing support. Several previous studies on transition to motherhood have referred to partner and family support and the changed relationships with them [ 9 , 11 , 12 , 13 ], with similar results to this study, which showed that building new relationships and connections was key. Conversely, a new finding of reflecting on child-rearing in the community was clarified as a transition condition, not only the relationships with partners and families.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was important for them to reflect on child-rearing in the community and build new relationships and connections to get the sense that child-rearing was not only an individual effort, but was also positioned in the community and society through child-rearing support. Several previous studies on transition to motherhood have referred to partner and family support and the changed relationships with them [ 9 , 11 , 12 , 13 ], with similar results to this study, which showed that building new relationships and connections was key. Conversely, a new finding of reflecting on child-rearing in the community was clarified as a transition condition, not only the relationships with partners and families.…”
Section: Discussionsupporting
confidence: 86%
“…Since most of the existing research on the transition to motherhood has studied white, married, and middle-class individuals, it is necessary to expand it to a wider range of socioeconomic classes and to more culturally diverse participants as they transition into motherhood [ 9 ]. Recently, there have been studies targeting adolescent mothers [ 10 ], blind women [ 11 ], women in wheelchairs [ 12 ], and women with infants with special care needs [ 13 ]. A review has shown that the transition to motherhood includes two inherent processes: (1) engagement and (2) growth and transformation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For women with disabilities, prejudice and discrimination related to the exercise of motherhood emerge in family and close relationsh ips 18,[32][33][34][35][37][38][39]41,42,44,[50][51][52][53]56,57,[60][61][62][64][65][66][67][68]70,76,77,79 .…”
Section: Infantilization Dehumanization and Discredit In Motherhood E...mentioning
confidence: 99%
“…La maternidad y la paternidad se consideran elementos complejos y son objeto de estudios a nivel nacional e internacional. En consecuencia, en los círculos científicos se han difundido con frecuencia numerosas ideas sobre la paternidad, lo que puede llevar a las madres y los padres a considerar que los modelos que han aprendido y utilizado ya no tienen ninguna validez o son inadecuados frente a los avances del país y del mundo (2).…”
unclassified
“…De esta manera, es posible reorganizar los papeles y funciones de los hombres y las mujeres con respecto al cuidado de los niños. La paternidad se inserta en un nuevo modelo de familia, que asume y reconoce la paternidad ofreciendo valor a la mujer, facilita el ciclo gravitatorio, haciendo que se produzcan intercambios afectivos y demostrando fragilidades para el hombre, demuestra seguridad y confianza, haciendo que se produzca la división de tareas entre la pareja, compromiso y apoyo a la mujer en todo el proceso de gestación, parto, alumbramiento, posparto y seguimiento del crecimiento y desarrollo del niño (1)(2)(3)(4).…”
unclassified